Inoculation of Chir (Pinus Longifolia) with Coleosporium Campanulae (Pers.) Lev., on Campanula Canesoens, Wall, and Coleos-porium Inulae (Kunze) Ed. Fish., on Inula Cappa D. C. - Khan, A. Hafiz (Indian Forester, 1928)
No abstract